Analysis of The Needs for Developing E-LKPD with The Concept of Heat Integrated with Ethnoscience and Joyfull Learning to Facilitate Students’ Knowledge and Communication Skills - Suci Agusfina Sari (Physics Learning and Education, 2026)
The development of science and technology (IPTEK) has brought significant changes in the world of education, especially in supporting the achievement of 21st century skills such as critical thinking, creativity, communication, and collaboration (4C). However, the results of the needs analysis at SMA Negeri 1 Enam Lingkung show that the use of technology-based learning devices, such as E-LKPD (Electronic Student Worksheets), is still not optimal. Teachers still predominantly use printed LKPDs that have not been integrated with the ethnoscience approach and joyful learning model, so they do not support the improvement of students' knowledge and communication skills. Students also experience various obstacles, such as difficulty understanding the material on the concept of heat, low learning outcomes, and communication skills that are still relatively low. This study uses a quantitative descriptive method to identify the needs of teachers and students for the development of E-LKPD on the concept of heat that is integrated with ethnoscience and joyful learning. The results of the analysis show the need to develop interactive and contextual E-LKPDs to facilitate the improvement of students' knowledge and communication skills, while supporting the implementation of the independent curriculum and 21st century learning.